La estimulación sensorio motriz y su incidencia en el desarrollo de la expresión oral y escrita de los niños y niñas del primer año de educación básica de la unidad educativa Tcrn. Lauro Guerrero de la ciudad de Loja durante el periodo, 2014-2015 lineamientos propositivos - Ortega Vivanco, Maritza Alexandra (2015)
This thesis refers to: SENSORY MOTOR STIMULATION AND ITS IMPACT ON THE DEVELOPMENT OF SPEAKING AND WRITTEN FOR CHILDREN OF THE FIRST YEAR OF BASIC EDUCATION EDUCATIONUNITTCRN. LAUROGUERREROLOJA CITY DURING PROACTIVE GUIDELINES 2014-2015. The central problem of the research was: ¿what is the impact the sensory motor stimulation in the development of oral and written expression children First-Year basic education of the Education Unit Tcrn. Lauro Guerrero, in the 2014-2015 academic year? The general objective was: to contribute to this research to improve the development of speaking and writing children's first year of basic education through the sensorimotor stimulation. The following methods were used for the preparation of this research: Deductive/Inductive, Descriptive, Scientific and Statistical Model, The techniques and instruments used were: poll applied to teachers to determine the sensory stimulation - driving;and the Test of Gross Ebee to assess psychomotor development of children; and the Test of Lourenco Filho applied to children of first year of basic education to determine the development of oral and written expression;. Of applied survey concludes that 100% of teachers say they rarely planned educational activities, integrations that induce sensorimotor stimulation for children First-Year Basic Education. And through the application of the Test of Gross Ebee whose results show that 82% of children have a psychomotor development very satisfactory, and 18% have a satisfactory psychomotor development. By Lourenco Filho test that determined the degree of development of oral and written children's first year of basic expression. This being a very satisfactory 62%, 33% and 5% moderately satisfactory satisfactory.